2021
DOI: 10.1097/lbr.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Fluoroscopic Bronchoscopy 2.0

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Our development of the AFB technique in HOR, which links the endobronchial road mapping of preprocedural CT and the target lesion derived from intraprocedural CBCT, presents a new platform for fluoroscopy-guided endobronchial intervention [ 20 ]. This new navigation technique provides the ease of visibility of small lung nodules and the location of lesions masked by other organs and differentiates AFB from standard fluoroscopic procedures [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our development of the AFB technique in HOR, which links the endobronchial road mapping of preprocedural CT and the target lesion derived from intraprocedural CBCT, presents a new platform for fluoroscopy-guided endobronchial intervention [ 20 ]. This new navigation technique provides the ease of visibility of small lung nodules and the location of lesions masked by other organs and differentiates AFB from standard fluoroscopic procedures [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CBCT-guided bronchoscopy (without ENB) for image-based navigation and 3D confirmation of tool-in-lesion was published by Verhoeven et al 22 Although a learning effect for CBCT-guided bronchoscopy with AF of the 3D segmented lesion was reported, the diagnostic accuracy increased over time from 72% to 90% 22 . In a recent research letter, Yang et al 23 reported on AF enhanced with the bronchial anatomy for image-guided endobronchial interventions. In their work, georeferencing of the bronchial anatomy from preoperative CT images with intraprocedural CBCT images was accomplished by manual calibration in the axial, coronal, and sagittal planes 23 …”
mentioning
confidence: 99%
“…In a recent research letter, Yang et al 23 reported on AF enhanced with the bronchial anatomy for image-guided endobronchial interventions. In their work, georeferencing of the bronchial anatomy from preoperative CT images with intraprocedural CBCT images was accomplished by manual calibration in the axial, coronal, and sagittal planes 23 …”
mentioning
confidence: 99%
See 1 more Smart Citation